Pengaruh Kombinasi Terapi Relaksasi Benson dan Murottal Al-Quran Terhadap Perubahan Tekanan Darah pada Pasien Hipertensi - Rika Dian Mustika; Erna Melastuti; Ahmad Ikhlasul Amal (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is a condition that often does not present clear visible symptoms, with blood pressure readings reaching 140/90 mmHg or higher. One non-pharmacological treatment method that can be considered to reduce hypertension is Benson relaxation therapy combined with Quranic recitation (murottal). This study aims to evaluate the effects of the combination of Benson relaxation therapy and Quranic recitation on blood pressure changes in hypertensive patients. The study design used a quasi-experimental quantitative approach with a pretest-posttest method without a control group. The sample was selected using purposive sampling, involving 21 hypertensive patients receiving treatment at the Sultan Agung Islamic Hospital. Wilcoxon test was used for data analysis. The results of the study showed that before the intervention, both systolic and diastolic blood pressure were in the stage 2 hypertension category, but after the intervention, blood pressure decreased to stage 1 hypertension. This indicates a significant change in blood pressure due to the combination of Benson relaxation therapy and Quranic recitation (p-value < 0.05).